1991
DOI: 10.1104/pp.97.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Photosynthetic Characteristics of Solanum tuberosum Plantlets Cultivated in Vitro in Different Conditions of Aeration, Sucrose Supply, and CO2 Enrichment

Abstract: Growth characteristics, oxygen exchange, and carbohydrate and chlorophyll contents were determined 30 days after subculturing of single node-derived plantlets of Solanum tuberosum cv Haig cultivated in vitro. Cultivation conditions were: (a) photomixotrophy in closed vessel, (b) photomixotrophy in closed vessel on medium supplemented with silver thiosulfate, (c) photomixotrophy in aerated vessel, (d) photoautotrophy in air, (e) photoautotrophy in C02-enriched air. In photomixotrophic conditions, aeration of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
29
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 19 publications
9
29
1
Order By: Relevance
“…Additionally, no assessed treatments produce more competent microshoots from the point of view of their similarity to plants grown in nursery conditions (seedlings). The results confirmed that using sucrose as external source of carbohydrates during proliferation stage of Castanea sativa microshoots had a positive effect on photosynthesis, chlorophyll content and growth, similar to that reported by Cournac et al [56]; Paul and Stitt [16]; and Ticha et al [17]. With this knowledge it is possible to establish strategies of mixotrophic culture that lead to production of competent microshoot during in vitro culture and, consequently, minimize the transfer stress and maximize the ex vitro survival rates.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, no assessed treatments produce more competent microshoots from the point of view of their similarity to plants grown in nursery conditions (seedlings). The results confirmed that using sucrose as external source of carbohydrates during proliferation stage of Castanea sativa microshoots had a positive effect on photosynthesis, chlorophyll content and growth, similar to that reported by Cournac et al [56]; Paul and Stitt [16]; and Ticha et al [17]. With this knowledge it is possible to establish strategies of mixotrophic culture that lead to production of competent microshoot during in vitro culture and, consequently, minimize the transfer stress and maximize the ex vitro survival rates.…”
Section: Resultssupporting
confidence: 91%
“…So, when the sugar export from the leaf is reduced, it will be stored in these organs. An explanation for the inhibition of photosynthesis might be the low rate of regeneration of the carboxylation substrate RuBP due to the accumulation of soluble sugar in the leaves [56]. Our results indicate that in LL LS an increase in the starch granules was concomitant with lower net photosynthesis.…”
Section: Discussionmentioning
confidence: 59%
“…However, grafting is time consuming, requires special skills and the success rates vary significantly. Roots induced from cut ends of shoots of chickpea were shorter in length in semisolid medium as compared to liquid medium, similar to the earlier reports (Jackson et al, 1991;Cournac et al, 1991;Ebrahim and Ibrahim, 2000;Hazarika, 2006). The retardation in root length in the semisolid medium may be attributed to the relatively lower aeration in agar-gelled medium as indicated by earlier researchers (Hazarika, 2006;Pati et al, 2006;Rout et al, 2006).…”
Section: Development Of Strong Root Systemsupporting
confidence: 86%
“…Assays of the soluble sugars (glucose, fructose and sucrose) were performed by the enzyme method described by Boehringer (1984 We observed that the hybrid walnut plantlets cultured on a medium with a high sucrose concentration had a high soluble carbohydrate content. It was similar to that observed in potato plantlets (Cournac et al, 1991) and in hop plants (Howard and Sykes, 1966). The high sucrose concentration also led to high dry matter accumulation in walnut plantlets but all plantlet parts were not affected similarly.…”
Section: Plantlet Productionsupporting
confidence: 86%